Age and growth of Arno goby, Padogobius nigricans (Canestrini, 1867), in the Aggia River (Umbria, Central Italy). (2nd February 2015) - Pompei, L.; Giannetto, D.; Lorenzoni, M.
Summary: In this study, data of Padogobius nigricans, a species endemic to Central Italy, were used to assess the age, growth parameters and condition of this species. Length–weight relationships are also provided and represent the first available reference in the literature for the Arno goby. Data were collected in the Aggia River, a tributary of the Tiber River, by monthly samplings. A total of 780 specimens ranging in size from 1.5 to 9.2 cm were analyzed. Age was assessed by examination of scales, with the maximum age of 4+ years observed in males and 3+ in females. Previous growth was determined by back‐calculation of scale measurements. The von Bertalanffy growth parameters were estimated separately for sexes (males: L ∞ = 9.759 cm, k = 0.505, t 0 = 0.025, Ф ′ = 1.682; females: L ∞ = 8.989, k = 0.458, t 0 = 0.028; Ф ′ = 1.599). Evidence of growth differences between sexes was found, with males living longer and reaching larger sizes. Using the relative condition factor, condition was lower in females than in males, especially during the breeding period due to the strain of high reproduction. Competition with the congeneric P. bonelli, a species endemic to Northern Italy that was introduced in Central Italy, seems not to have been disadvantaged directly by the growth of P. nigricans in the Aggia River, since no selective size‐mortality occurred in the population.